Design of Dispersing Processes Using a Newly Developed Dispermeter. Issue 7 (6th June 2013) - Schönstedt, B.; Schilde, C.; Beinert, S.; Kwade, A.
Abstract Typically, the product fineness in a dispersion process is determined by the strength of the agglomerates and aggregates, the properties of the homogeneous phase and its interaction with the surface of the disperse phase, the stress mechanism itself as well as its intensity and frequency acting on the particles. The objective of this study is to characterize the efficiency of a dispersion process in terms of stress frequency and intensity using a newly developed dispersing machine called dispermeter. This dispersing machine is capable of processing suspensions with a broad range of viscosities. Furthermore, due to highly defined geometries, the rheological behavior of suspensions as an important parameter for processability and suspension stability can be characterized during the dispersion process. By utilizing the rheological properties the dispermeter can be used for the selection of an applicable electrostatic or steric stabilizer for an optimal dispersion process. With the dispermeter two different types of pyrogenic metallic oxide particles, nanosized alumina and silica, are processed. The progress in deagglomeration is monitored by particle size analysis and compared with that in a dissolver. A theoretical process model is used to characterize both processes. Moreover, this model is used to predict the dispersion results obtained in the dissolver.